Korupcja przeszkodą w walce z narkotykami - Vilks, Andrejs; Kipāne , Aldona (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2020)
The article provides an insight into drug-related corruption as a social legal phenomenon. The aim of the article is to provide the criminological framework of drug-related corruption by analyzing theoretical and practical problems. The subject of the study is corruption as a negative social phenomenon related to the illicit trafficking in narcotic drugs, as well as directions of prevention of this phenomenon. Drug-related corruption is a relatively new criminological concept. Taking into consideration that one of the most difficult problems today is the prevention of crime, analysis of these phenomena is an important subject of research within criminology. Therefore, constant criminological analysis of this negative phenomenon is necessary by identifying preventive measures, methods and measures. The content of various documents, opinions and scientists‘ perspectives form the basis for this research. The authors used several methods of general scientific research and the following specific methods: monographic, logically constructive method, logical interpretation, statistical methods and method of interpretation of legal norms.